HiChIP-Peaks: a HiChIP peak calling algorithm - Shi, Chenfu (Bioinformatics, 2020)
MOTIVATION: HiChIP is a powerful tool to interrogate 3D chromatin organization. Current tools to analyse chromatin looping mechanisms using HiChIP data require the identification of loop anchors to work properly. However, current approaches to discover these anchors from HiChIP data are not satisfactory, having either a very high false discovery rate or strong dependence on sequencing depth. Moreover, these tools do not allow quantitative comparison of peaks across different samples, failing to fully exploit the information available from HiChIP datasets. RESULTS: We develop a new tool based on a representation of HiChIP data centred on the re-ligation sites to identify peaks from HiChIP datasets, which can subsequently be used in other tools for loop discovery. This increases the reliability of these tools and improves recall rate as sequencing depth is reduced. We also provide a method to count reads mapping to peaks across samples, which can be used for differential peak analysis using HiChIP data. AVAILABILITY AND IMPLEMENTATION: HiChIP-Peaks is freely available at https://github.com/ChenfuShi/HiChIP_peaks. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.